Paul's Online Notes
Paul's Online Notes
Home / Algebra / Solving Equations and Inequalities / Absolute Value Equations
Show Mobile Notice Show All Notes Hide All Notes
Mobile Notice
You appear to be on a device with a "narrow" screen width (i.e. you are probably on a mobile phone). Due to the nature of the mathematics on this site it is best views in landscape mode. If your device is not in landscape mode many of the equations will run off the side of your device (should be able to scroll to see them) and some of the menu items will be cut off due to the narrow screen width.

Section 2.14 : Absolute Value Equations

3. Solve the following equation.

\[6u = \left| {1 + 3u} \right|\]

Show All Steps Hide All Steps

Hint : Just because the quantity outside of the absolute value bars in not a number does not mean this problem works any differently. Just remember to be careful with your answers!
Start Solution

Despite the fact that the quantity outside of the absolute value bars is not a positive number doesn’t mean that we can’t use the same process that we used in the first two problems.

Using the formula from the notes gives,

\[1 + 3u = - 6u\hspace{0.25in}{\mbox{or}}\hspace{0.25in}1 + 3u = 6u\] Show Step 2

Now solving each these linear equations gives,

\[\begin{align*}1 + 3u & = - 6u & \hspace{0.25in} & {\mbox{or}} & \hspace{0.25in}1 + 3u & = 6u\\ 1 & = - 9u & \hspace{0.25in} & {\mbox{or}} & \hspace{0.25in}1 & = 3u\\ u & = - \frac{1}{9} & \hspace{0.25in} & {\mbox{or}} & \hspace{0.25in}u & = \frac{1}{3}\end{align*}\] Show Step 3

Now, because the quantity outside of the absolute value bars was not a positive constant we need to be careful with the answers we got in the previous step. It is possible that one or both are not in fact solutions to the original equation. So, we need to verify each of the possible solutions from the previous step by checking them in the original equation.

\[u = - \frac{1}{9}:\,\,\,\,\,\,\,\,6\left( { - \frac{1}{9}} \right)\mathop = \limits^? \left| {1 + 3\left( { - \frac{1}{9}} \right)} \right|\,\,\,\,\,\,\,\, \to \,\,\,\,\,\,\, - \frac{2}{3}\mathop = \limits^? \left| {\frac{2}{3}} \right|\,\,\,\,\,\,\, \to \,\,\,\,\,\,\, - \frac{2}{3} \ne \frac{2}{3}\hspace{0.25in}{\mbox{NOT}}{\mbox{ OK}}\] \[u = \frac{1}{3}:\,\,\,\,\,\,\,\,6\left( {\frac{1}{3}} \right)\mathop = \limits^? \left| {1 + 3\left( {\frac{1}{3}} \right)} \right|\,\,\,\,\,\,\,\, \to \,\,\,\,\,\,\,2\mathop = \limits^? \left| 2 \right|\,\,\,\,\,\,\, \to \,\,\,\,\,\,\,2 = 2\hspace{0.25in}{\mbox{OK}}\]

Therefore, the only solution to the original equation is then : \(\require{bbox} \bbox[2pt,border:1px solid black]{{u = \frac{1}{3}}}\) .